La decisione del medico del lavoro: tra norme, valori etici e prove scientifiche / Occupational physician’s decisions on the basis of legislation, ethics and scientific evidence - Franco, G. (La Medicina del Lavoro, 2009)
Il contributo analizza la relazione tra (i) norme alle quali il medico del lavoro deve attenersi (attuare interventi che tengano conto dei risultati della ricerca scientifica e ispirare le proprie attività ai principi del codice etico), (ii) valori etici (basati sui principi di promozione del bene, autonomia e giustizia) ai quali il medico deve aderire e (iii) le informazioni (da utilizzare in modo coscienzioso, giudizioso ed esplicito) alle quali fare riferimento per prendere decisioni. Occupational physician’s decisions on the basis of legislation, ethics and scientific evidence Background: In the dynamic context of occupational medicine an increasing number of occupational health problems requires a high-quality standard practice supported by decisions consistent both with ethics and legislation. Objectives: This paper examines the relationship between legal requirements, ethical values and scientific evidence issues in occupational health practice. Results: i) Legal requirements. Italian law states that practice must be evidence-based and comply with the code of ethics for occupational health professionals of the ICOH. ii) Ethical values. The code itself emphasizes that practice should be relevant, knowledge-based, sound and appropriate to occupational risks. Furthermore, the objectives and methods of health surveillance and biological monitoring must be clearly defined and indicators must be chosen according to their relevance and predictive value. Any dilemma arising from the practice should be dealt with according to the ethical principles of health benefit, independence and justice. iii) Scientific evidence. Both the law and the code of ethics require that practice be based on available evidence. Conclusions: Decisions made on the basis of a comprehensive process founded on scientific evidence should result in effective and high-quality outcomes that respect both the law and the rights of individuals and society.